Radial intensity gradients of galactic cosmic rays in the heliosphere at solar maximum: 1D no-shock simulation - O. G. Morales-Olivares (Geofísica Internacional, 2009)
We study the spatial distribution of galactic cosmic rays in the heliosphere at solar maximum of cycles 21, 22 and 23, using a one-dimensional no-shock model of the cosmic ray transport equation. We investigate the radial intensity gradients from 1 AU to the distant heliosphere and interpret the data from IMP8, Voyagers 1 and 2, Pioneer 10 and balloon experiment BESS. We consider three physical processes that affect cosmic radiation: diffusion, convection and adiabatic energy loss. Our analysis indicates that adiabatic energy may play an important role in the radial distribution of galactic cosmic rays in the inner heliosphere. In the outer region diffusion and convection are the dominant processes.